The limnology and plankton of two saline lakes in the Parque Luro Reserve, La Pampa Province (argentina) (Semiárida, 2023)
In La Pampa province, limnological studies have been carried out in saline lakes, generally located in basins with agricultural exploitations. In Parque Luro Provincial Reserve there are two scarcely studied saline lakes: East and West Lakes. The objective was to analyze physical-chemical parameters and those of the plankton of these protected environments and compare them with other Pampean lakes under different anthropic influence. Monthly samples were collected between October 2014 and September 2015. In both lakes, Cl- and Na+ predominated, but salinity differed (East: 276.53 ±42.00 g/L, West 29.33 ±10.25 g/L). West Lake was covered by the macrophyte Ruppia cirrhosa and water was transparent. Accumulated phytoplankton richness was 30 taxa, and was negatively influenced by salinity, since the highest richness (22 taxa) was that of West Lake. In both lakes the most frequent species were Dunaliella salina and D. viridis. Fourteen taxa were found in zooplankton of both lakes, and richness was also influenced by salinity. In East Lake only Artemia persimilis was recorded and in West Lake the typical association of mesosaline Central Argentine lakes was recorded, in low density due to the dense coverage of the macrophyte.
Keywords: hypersaline lakes; mesosaline lakes; protected areas; Artemia persimilis; Dunaliella salina; Ruppia cirrhosa